Occupational mobility, occupation distance and specific human capital - Chris Robinson (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2011)
Measures of occupation distance based on underlying skill portfolios are constructed and used to contrast involuntary and total mobility. One component of total occupational mobility is voluntary mobility, including moves to higher job offers using the same skills, as well as promotions that may reflect augmented skills. These are not sources of specific human capital loss. By contrast, the involuntary mobility component due to plant closure involves a higher incidence of loss of specific capital. The evidence indicates that a decreasing fraction of occupation switches involve significant skill portfolio switches: the mean distance in involuntary occupational mobility declines significantly over time. Wage losses following displacement are strongly related to distance. This is reflected in a marked downward shift in the skill portfolio for involuntary occupation switchers. By contrast, the direction of the skill portfolio change in total mobility shows a neutral or modest upward pattern, suggesting limited specific human capital loss from voluntary occupational mobility.
Keywords: J24; J31; 330; Arbeitsmobilität; Arbeitsplatz; Entfernung; Qualifikation; Kündigung; Lohnniveau; Kanada